Tafsir Moral Dalam Kidung Pangiling Karya Kiai Imam Malik - Miftakhur Ridlo (Nazhruna: Jurnal Pendidikan Islam, 2019)
Kiai Imam Malik is the author of Kidung Pangiling who resides in Losari village, Mojosari district, Mojokerto district. He founded a hermitage named Padepokan Mayangkoro Islamic Boarding School Connect Sari Noto Projo Majapahit Bangkit Nusantara Jaya. This Pangiling Song is a syiiran who is used to being heard and charged through active speakers in the Wisnu Manunggal Mosque which is held every morning and evening. Kiai Imam Malik created the pangiling hymn aimed at giving advice and reminders to the people during the 1997 - 2006. The moral interpretation in Kidung Pangiling by Kiai Imam Malik broadly explained the phenomenon of morality which experienced tremendous degradation that occurred in society. Especially in 1999, 2000 and 2001, because there were civil wars in several places, such as in Kalimantan, Sulawesi and Ambon. Several verses in song : Akeh wong kalab gak podho kroso Mulai sasi songo tahun 99 Wis podho bingung wedi ciloko Ora biso nyukuri nikmat seng teko, Tatanan anyar sing salah kaprah Sing wis dadi umum, bener tak lumrah Sebab ilange hukum lan sejarah Karek ngenteni tekane banjir darah.